2012
DOI: 10.1016/j.fct.2012.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Gastroprotective and toxicological evaluation of the Lithothamnion calcareum algae

Abstract: Lithothamnion calcareum is a red alga of the Corallinacea family whose main feature is the formation of calcium carbonate precipitate in its cell walls. L. calcareum is marketed as a nutritional supplement for calcium and other minerals in Brazil and other countries under the pharmaceutical name of Vitality 50+. In this study, gastroprotective and pre-clinical toxicity assays were performed on this product. Doses of 30, 120 and 480 mg/kg were used in the gastroprotective study on Wistar rats. A dose of 2000 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Mice are often used in acute toxicity studies9 [ 14 ] and were also deemed appropriate for the purposes of this study. Significantly, this is a higher dose level than the LD 50 level already published (2 g/kg BW in rats) [ 11 ]. Although acute toxicity studies often test doses in the range of 5 g/kg BW [ [12] , [13] , [14] ], a higher dose was chosen for this study based on preliminary studies that indicated very low toxicity for this particular product.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Mice are often used in acute toxicity studies9 [ 14 ] and were also deemed appropriate for the purposes of this study. Significantly, this is a higher dose level than the LD 50 level already published (2 g/kg BW in rats) [ 11 ]. Although acute toxicity studies often test doses in the range of 5 g/kg BW [ [12] , [13] , [14] ], a higher dose was chosen for this study based on preliminary studies that indicated very low toxicity for this particular product.…”
Section: Discussionmentioning
confidence: 87%
“…However, published comprehensive toxicological data on Lithothamnion sp. calcium are sparse, excepting one other publication [ 11 ], and given the wide-ranging applications of this bioavailable source of calcium and other minerals, completing and publishing these studies was deemed important.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 20 On the other hand, oligo-elements function to balance the nervous system as demonstrated by several studies conducted to establish the efficacy of single trace elements. 21 , 22 …”
Section: Introductionmentioning
confidence: 99%